Improvement of engine performance using Diethylene Glycol Dimethyl Ether (Dgm) as additive - Nabi, Md. Nurun; Chowdhury, Md. Wahid (Penerbit UTM Press, 2006)
This Research Work Investigates Diesel Combustion And Exhaust Emissions With Additives Addition To Conventional Diesel Fuel In A Four-Stroke Naturally Aspirated Direct Injection (DI) Diesel Engine. The Additives Include DGM, And Liquid Cerium. The Results Show That With The Addition Of DGM To Diesel Fuel, Brake Specific Energy Consumption (BSEC) And All Diesel Emissions Are Significantly Reduced. The Volumetric Blending Ratios Of Additives To Diesel Fuel Are 0, 25, 50, 75 And 100%. All Emissions Including Smoke Emissions Decrease With The Increase In Oxygen Content In The Fuel And It Is Noted That Smoke Emission Completely Disappeared At An Oxygen Content Of 36 Wt-%. The Reason For Improvement In BSEC With The Addition Of Additives To Base Diesel Fuel Is The Improvement Of Degree Of Constant Volume Combustion, And The Reduction Of The Cooling Loss. Engine Noise And Odor Concentrations Are Remarkably Reduced With Diesel-Additive Blends. Significant Improvement In BSEC And Exhaust Emissions Is Not Only Found At Medium Load Condition But Also At High Load Condition.